Economic stratification and hierarchy among US colleges and universities - Gordon C. Winston (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2000)
Colleges and universities in the US differ markedly in their access to economic resources, hence in what they can do for their students. National (IPEDS) data are used here to describe the resulting hierarchy that?s reflected in schools? spending on their students, the prices those students pay, and the subsidies they get in consequence. Both historical data and projections based on recent institutional saving suggest that economic disparities among institutions and their students are increasing. In a final section, the paper asks what to make of this: what we can say about ?the right degree? of institutional disparity, so whether we have too much, too little, or about the right amount of differentiation.
Keywords: 330; Hochschulfinanzierung; Kosten; Subvention; Studienfinanzierung; Vergleich; USA